Enhancing methanogenesis of anaerobic granular sludge by incorporating Fe/Fe oxides nanoparticles aided with biofilm disassembly agents and mediating redox activity of extracellular polymer substances. (1st June 2022) - Li, Naiyu; Quan, Xiangchun; Zhuo, Meihui; Zhang, Xiangfeng; Quan, Yanping; Liang, Peng
Highlights: Biofilm disassembly agents helped to incorporate more Fe/Fe oxides into AGS. Loading Fe/Fe oxides promoted flavins and c-Cyts secretion in EPS of AGS. The resistance of EPS was reduced and interspecies electron transfer was increased. AGS with Fe/Fe oxides showed an enhanced methane production capacity. ABSTRACT: Anaerobic granular sludge (AGS) is a promising technology for organic wastewater treatment and energy recovery. In this study, three different kinds of Fe and Fe oxides nanoparticles (Fe3 O4, Fe2 O3 and ZVI) were tried to be incorporated into AGS through direct loading or aided with biofilm disassembly agents of norspermidine and D-tyrosine, which was aimed to enhance methane production capacity of AGS via increasing redox activity of extracellular polymer substance (EPS) and interspecies electron transfer. Despite the loading methods, incorporation of Fe and Fe oxides nanoparticles into AGS increased methane production capacity remarkably, with an enhancement of 36.49–85.17%, 20.37–204.95% and 189.71–243.32%, respectively, for the Fe3 O4, Fe2 O3 and ZVI loaded AGS. Pretreatment of AGS using biofilm disassembly agents helped to incorporate more Fe and Fe oxides into the inner structure of AGS, which further enhanced methane production capacity by 48.68% and 184.58%, respectively, for the Fe3 O4 and Fe2 O3 loaded AGS. Loading Fe and Fe oxides into AGS not only introduced exogenous conductive substances and Fe(III)/Fe(II) redox couples into EPS matrix of AGS, but also stimulated the production of redox active components of flavins and c-Cyts. All these factors may contribute to the reduced resistance of EPS, enhanced interspecies electron transfer and methane production capacity of AGS. This study provides a novel strategy and facile method to accelerate interspecies electron transfer and enhance methane production for matured AGS. Graphical Abstract: Image, graphical abstract .